Analysis Of Majaz Mursal On Meaning In The Interpretation Of The Qur'an: Analisis Majaz Mursal Terhadap Makna Dalam Penafsiran Al-Qur’an - Aulia Fitri; Rahmad Hidayat; Azamel Fata; Erwin Saputra Andika; Rahmi Umaira (Institut Agama Islam Sumatera Barat Pariaman, 2025)
This paper analyzes majaz mursal in relation to the interpretation of majaz in the Qur'an. Majaz is considered very important in interpreting the verses of the Qur'an. However, the existence of majaz has sparked much debate among scholars. The reason for this is that many scholars are considered to have exaggerated the use of majaz, thereby straying from the intended meaning of a verse. Zamaksyari is one of the scholars who is an expert in the study of balaghah, tafsir, and Arabic language. This study uses the library research method by referring to Zamaksyari's work, Tafsir al-Kasyaf, an interpretation of the Holy Qur'an, including the meaning of majaz mursal in interpreting and understanding Qur'anic verses. Research shows that Zamaksyari is a figure who acknowledges the existence of majaz in the interpretation of the Qur'an. The application of majaz can be seen in several verses of the Qur'an, namely; Surah Ghāfir [40]: 13, Surah an-Nisā' [4]: 92, Surah an-Nisā' [4]: 2, and Surah Yusuf [12]: 36